Routine dynamics in action replication and transformation - Feldman, Martha S. 1953-; D'Adderio, Luciana; Dittrich, Katharina 1983-; Jarzabkowski, Paula (Research in the Sociology of Organizations, 2019)
Contains an Open Access chapter.This book explores central themes in the enactment and coordination of organizational routines, including replication and transfer, ecologies and interdependence, action and the generation of novelty and technology and sociomateriality.